Inhibition of microRNA-429 in the renal medulla increased salt sensitivity of blood pressure in Sprague Dawley rats. Issue 9 (September 2017) - Zhu, Qing; Hu, Junping; Wang, Lei; Wang, Weili; Wang, Zhengchao; Li, Pin-Lan; Boini, Krishna M.; Li, Ningjun
Abstract : Background: We have previously shown that high salt intake suppresses the expression of prolyl hydroxylase domain-containing protein 2 (PHD2), an enzyme promoting the degradation of hypoxia-inducible factor (HIF)-1α, and increases HIF-1α along with its target genes in the renal medulla, which promotes sodium excretion and regulates salt sensitivity of blood pressure. However, it remains unknown how high salt inhibits the expression of PHD2. Method and results: The current study first revealed that high-salt-induced PHD2 inhibition was due to the enhanced decay of mRNA. We then found that high salt significantly increased the expression of miR-429, which was subsequently proven to target the 3′-untranslated region of PHD2 and reduce PHD2 levels, in the renal medulla. To define the functional role of renal medullary miR-429 in the regulation of PHD2/HIF-1α-mediated renal adaptation to high salt intake and salt sensitivity of blood pressure, we locally inhibited miR-429 in the renal medulla by locked nucleic acid anti-miR-429 in uninephrectomized rats. Our results demonstrated that inhibition of miR-429 remarkably increased the levels of PHD2, which disrupted PHD2-associated adaptive activation of HIF-1α-mediated gene expression in response to high salt in the renal medulla and consequently inhibited urinary sodium excretion, enhanced sodium retention in response to chronic sodium overloading, and as a result, produced a salt-sensitive hypertension. Conclusion: It is concluded that miR-429 is an important upstream mediator in PHD2/HIF-1α-associated renal adaptation to high salt intake and that deficiency in miR-429-mediated PHD2 inhibition in response to high salt in the renal medulla may represent a pathogenic mechanism for salt-sensitive hypertension.